Collections - Jordan Schnitzer Museum of Art (2011)
[Dt.:] Die Sammlung des JSMA gründet auf der Murray Warner Collection of Oriental Art. Sie umfasst asiatische Objekte aus China, Japan und Korea. Der Schwerpunkt des Museums liegt auf asiatischer Kunst, den zweiten Schwerpunkt bildet die Sammlung Moderner und Zeitgenössischer Kunst Amerikas. Ausserdem gibt es eine Sammlung Moderner Malerei aus Europa und Russischer Ikonen. In der Onlinedatenbank sind alle Werke zugänglich. - [Engl.:] The JSMAs permanent collection features objects bridging the cultures of the East and West. Beginning with the Murray Warner Collection of Oriental Art, Asian objects, primarily from China, Japan, and Korea the museum has significantly expanded its holdings of Asian fine and decorative arts and has welcomed major collections of Pacific Northwest Art, including more than 500 works by Morris Graves. Also european paintings, modern and contemporary american art and russian icons. You can find all these works in the picture database of the museum online.